Biochar Reduces Zinc and Cadmium but not Copper and Lead Leaching on a Former Sewage Field. Issue 6 (1st November 2014) - Schweiker, Carolin; Wagner, Anne; Peters, Andre; Bischoff, Wolf‐Anno; Kaupenjohann, Martin
Abstract : The leaching of trace metals from anthropogenically contaminated sites poses the risk of groundwater pollution. Biochar has recently been proposed as a soil additive to reduce trace‐metal concentrations in the soil solution and to increase water retention, thus reducing drainage. However, field studies on the effects of biochar addition on trace‐metal leaching are scarce. Therefore, we added 0, 1, 2.5, and 5 g 100 g −1 of biochar derived from giant miscanthus ( Miscanthus × giganteus J.M. Greef & Deuter ex Hodk. & Renvoize) to soil contaminated by former wastewater irrigation and examined water retention and cumulative leaching of Zn, Cd, Cu, and Pb in a 2‐yr field study. Cumulative trace‐metal leaching was determined by self‐integrating accumulators (SIAs) based on ion‐exchange resins and compared with data calculated from mean concentrations in the soil solution collected with tension lysimeter plates and groundwater recharge rate. The highest rate of biochar addition increased water retention and thus reduced the amount of drainage water. Mean cumulative Zn and Cd fluxes decreased due to both reduced concentrations in the soil solution and reduced drainage. Although Cu and Pb concentrations in the soil solution increased with biochar addition, the reduced drainage resulted in similar fluxes in the biochar and the control treatment. The cumulative Zn, Cd, and Cu fluxes determined with SIAs were in the same range as the calculated values, while SIA‐based Pb fluxes were much higher than those calculated. Since the suction plates excluded colloids, the high SIA‐based Pb fluxes indicate colloidal transport and reveal the importance to elucidate the colloidal pathway for risk assessment.